(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This research seeks to find out the role of the administrative planning function in achieving sustainable development in pharmaceutical companies, where the researcher presented the results of statistical analysis using the statistical program(SPSS) version 25 based on the data of 220 questionnaire forms. The results of the research concluded that: - There is an impact of administrative planning (strategic planning) on the sustainable development of pharmaceutical companies. - There is an impact of management planning (tactical planning) on the sustainable development of pharmaceutical companies. - There is an impact of administrative planning (practical planning (implementation) on the sustainable development of pharmaceutical companies. Therefore, there is an impact of administrative planning on the sustainable development of pharmaceutical companies.